Coping with Firewood Scarcity in Soroti District of Eastern Uganda - Egeru, Anthony; Kateregga, Eseza; Mwanjalolo Majaliwa, Gilber Jackson (Open Journal of Forestry, 2014)
This study investigated how rural households cope with firewood scarcity in dryland areas of Eastern Uganda. A household survey was conducted in December 2008 to January 2009, where 490 respondents were randomly interviewed. Focus Group Discussions (FGDs) were also held with community elders and women. Responses were analyzed both descriptively and qualitatively. Findings indicated that 99% of the households used firewood for cooking with a per capita consumption of 542.32 Kilograms. Commonly used tree species included Combretnum molle (42.7%) and Acacia polyacantha willd (18.2%). Over 78% of the households have a preference for acacia tree species for firewood. In particular, Acacia polyacan-tha willd (60.3%), Acacia hockii (16.9%) and Combretum collinum (9.6%) were the most preferred tree species. The scarcity of firewood supply was eminent from the average distance (2 ± 7 Km) traveled by collectors in search of them. Firewood collectors spent 1 to 10 hours with an average of 3 hours weekly in firewood collection activities. This resulted in per annum estimated opportunity cost of Shillings 432,000 (US 232 dollars) for those who collected on weekly basis and Shillings 1,080,000 shillings (US 580 dol-lars) for those who collected on daily basis. The frequency of collection decreased as distance increased among 89% of the households. Minority of households (1%) have resorted to deliberately planting trees on their own farms to ease problems of firewood shortage, and to modification of biomass stove so as to use less firewood. Households in their endeavour to circumvent the problem of continued scarcity have resorted to poorer quality tree/bushes for firewood (71.2%), alongside other coping strategies such as cooking meals once a day, avoidance of cooking some food types (70%), and using crop residues as fuel source (60%). There is a need for scaling-up on-farm tree planting as well as the use of improved biomass cook stoves in the region.
Keywords: Adaptations; Household Energy; Firewood Scarcity; Soroti Uganda